Black's dictionary of physical education and school sport - Williams, Gareth 1960-. (London A&C Black, 2010)
"This dictionary is a key resource for students of Physical Education, School Sport and Sports Science at undergraduate level, facing new concepts and terminology. Over 100 entries cover all the key topics in this diverse subject area. The A-Z format makes it accessible and essential reading for anyone planning a career in teaching PE. Each entry is 300-500 words and includes practical teaching ideas and tips and further reading suggestions. All the theoretical concepts of social, political, economic and cultural influences are covered and the dictionary includes updates on recent key issues in Physical Education, including material on gifted and talented teaching, and junior athletic education."--Publisher's description.
Keywords: Physical education and training -- Dictionaries; Physical education and training